Heat transport analysis of aluminum alloy and magnetite graphene oxide through permeable cylinder with heat source/sink. (30th July 2020) - Ramesh, G K; Shehzad, S A; Rauf, A; Chamkha, A J
Abstract: The flow through a stretchable cylinder has auspicious uses in many industrial processes like thermal processing of food particles, liquid coating on photographic films and tubular heat exchangers. Motivated from these applications, heat transport through a stagnation-point hybrid nanoliquid flow past a permeable cylinder is scrutinized. Aluminum alloy and magnetite graphene oxide with water-based nanoparticles are considered. A uniform heat source/sink term is added in the energy equations. The noted novelty of this work is the application of the hybrid nanofluid along with the heat generation/absorption effect for stretchable cylinders which has not been considered in the open literature. The strong form of ordinary differential coupled equations is solved by the Runge–Kutta-Fehlberg-45 (RKF-45) numerical approach via the shooting technique. Graphical profiles are obtained and discussed at diverse physical parameters. Moreover, the drag friction and the Nusselt number are computed. The results have shown that the higher variation in ϕ 2 causes a reduction in the velocity and an enhancement in the temperature curves. Further, it is noted that the velocity curves of magnetite graphene oxide is higher than aluminum alloy nanoparticles. The Nusselt number is larger for the aluminum alloy nanoparticles case as compared to the values achieved for the case of magnetite graphene oxide nanoparticles.